Voltage tuning of photoinduced charge transfer resonances between 2,2′-bipyridine and a nanostructured silver electrode. - Valdivia Mantas, Samuel; Aranda, Daniel; Otero-Fernández-de-Molina, Juan Carlos; López-Tocón, Isabel (My University, 2023)
The effect of applied electric potentials and excitation wavelengths (785, 532, 473 nm) on the Surface-Enhanced Raman scattering (SERS) of 2,2′-bipyridine (2,2′-bpy) adsorbed on a silver electrode has been analyzed on the basis of a charge transfer (CT) resonance mechanism. DFT/TD-DFT calculations performed for a simple model of surface complex (Ag2-2,2′-bpy) point out that 2,2′-bpy preferably adsorbs through both nitrogen atoms in a cis-conformation with edge-on orientation. The calculated spectra in resonance with the two first bright metal-to-molecule charge transfer electronic states (CT0;B1 and CT1;B1) account for the main experimental features: the selective enhancement of the totally symmetric modes recorded at about 1585, 1560 and 1480 cm−1 under 532 nm line, staying the 1560 cm−1 band as the most intense under 473 nm line at more negative electrode potential. The split of SERS bands recorded in the 1600, 1000 and 600 cm−1 regions point to the existence of a monodentate coordination of the cis-conformer. The calculated resonance condition up to CT0 and CT1 states is fulfilled under 532 and 488 nm excitation lines, respectively, agreeing with the behaviour of the intensity-potential profile of the bands for each excitation wavelength.
Keywords: Química física; Efecto Raman de superficie intensificada; Química de superficies; Transferencia de carga; Electrodos; SERS spectroscopy; Charge transfer mechanism; Silver electrode; DFT/TD-DFT calculations; 2′-Bipyridine